2014
DOI: 10.1007/s10047-014-0776-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome (ARDS) treated successfully by veno-venous extracorporeal membrane oxygenation (ECMO) in a nearly drowned patient

Abstract: This report highlights about one acute respiratory distress syndrome (ARDS) case after near-drowning resuscitated using extracorporeal membrane oxygenation (ECMO). Few cases have been reported about ECMO use for near-drowning and in most of these cases, ECMO was initiated within the first week. However, in our report, we would like to emphasize that seemingly irreversible secondary worsening of ARDS after nearly drowned patient was successfully treated by ECMO use more than 1 week after near-drowning followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Among nontraumatic ARDS patients, the outcomes of the near‐drowning cases who suffered cardiac or pulmonary failure were good. Usually, near‐drowning events occur in otherwise healthy young subjects, and some authors have reported that ECMO support is useful even during the late phase of ARDS . Interestingly, one case of hanging was included in the nontraumatic group.…”
Section: Discussionmentioning
confidence: 99%
“…Among nontraumatic ARDS patients, the outcomes of the near‐drowning cases who suffered cardiac or pulmonary failure were good. Usually, near‐drowning events occur in otherwise healthy young subjects, and some authors have reported that ECMO support is useful even during the late phase of ARDS . Interestingly, one case of hanging was included in the nontraumatic group.…”
Section: Discussionmentioning
confidence: 99%
“…1a, d), suggesting that liver abscess might cause a diaphragmatic elevation, abnormal respiratory pattern and increased pulmonary vascular permeability on day 1. The use of ECMO to treat acute respiratory failure is increasing [8][9][10]. V-VECMO adult patients with sepsis-induced acute respiratory failure or pneumonia is not rare, while veno-arterial ECMO for adult patients with refractory septic shock is rare and remains unsatisfactory [11].…”
Section: Discussionmentioning
confidence: 99%
“…Olguda öykünün derinleştirilmesiyle ilk yakınmasının fenalık hissi olduğu ve ardından bayıldığı, başına soğuk su dökülerek kendine geldiği sırada şiddetli nefes darlığı olduğu öğrenildiğinden ayırıcı tanıda düşünülmesi gereken bir diğer durum ise su aspirasyonuna sekonder solunum yetmezliği tablosudur. Literatürde, olgumuzda olduğu şekilde su aspirasyonu olan bir olguya rastlanmamış ancak, tatlı veya tuzlu su aspirasyonu sonucu gelişen ölümcül veya ölümcül olmayan boğulma olguları tanımlanmıştır (17)(18)(19). Ölümcül olmayan boğulma olgularında, aspire edilen suyun niteliğinden bağımsız olarak, alveolokapiller membranın bütünlüğünde bozulmaya ve artmış geçirgenliğe bağlı olarak gelişen pulmoner ödem, değişen derecelerde hipoksemiye ve hatta ARDS tablosuna yol açmaktadır (17,20).…”
Section: Olguunclassified